The transaction avoidance regime in the recast European insolvency regulation: Limits and prospects. Issue 2 (30th July 2019) - Casasola, Oriana
Abstract: In the last decade, transaction avoidance in insolvency law has been in the limelight of the academic discussions. In particular, the scholarship has highlighted how the European Insolvency Regulation gives rise to several private international law issues. Moreover, the scholarship has explored solutions to these issues and proposed to harmonise the regime of transaction avoidance at European Union level. However, the recent legislative developments on the cross‐border insolvency law seem resistant to the proposed harmonisation. This article focuses on the transaction avoidance regime in the Recast European Insolvency Regulation. In particular, it seeks to evaluate whether the Recast has solved the issues arising within the original European Insolvency Regulation in relation to transaction avoidance. Secondly, it questions the suitability of the private international law approach to transaction avoidance in cross‐border insolvency within the European Union framework. The research suggests that the efforts required to the private international law framework to deal efficiently with transaction avoidance make the harmonisation of the regime of transaction avoidance at the European Union level a more appealing option.